The Role of Immunobiotics and Postbiotics in the Recovery of Immune Cell Populations From Respiratory Mucosa of Malnourished Hosts: Effect on the Resistance Against Respiratory Infections - Salva, Susana; Kolling, Yanina; Ivir, Maximiliano; Gutiérrez, Florencia; Alvarez, Susana (Frontiers in Nutrition, 2021)
Malnutrition is associated with a state of secondary immunodeficiency, which is characterized by a worsening of the immune response against infectious agents. Despite important advances in vaccines and antibiotic therapies, the respiratory infections are among the leading causes of increased morbidity and mortality, especially in immunosuppressed hosts. In this review, we examine the interactions between immunobiotics-postbiotics and the immune cell populations of the respiratory mucosa. In addition, we discuss how this cross talk affects the maintenance of a normal generation of immune cells, that is crucial for the establishment of protective innate and adaptive immune responses. Particular attention will be given to the alterations in the development of phagocytic cells, T and B lymphocytes in bone marrow, spleen and thymus in immunosuppression state by protein deprivation. Furthermore, we describe our research that demonstrated that the effectiveness of immunobiotics nasal administration in accelerating the recovery of the respiratory immune response in malnourished hosts. Finally, we propose the peptidoglycan from the immunobiotic Lactobacillus rhamnosus CRL1505 as the key cellular component for the effects on mucosal immunity, which are unique and cannot be extrapolated to other L. rhamnosus or probiotic strains. In this way, we provide the scientific bases for its application as a mucosal adjuvant in health plans, mainly aimed to improve the immune response of immunocompromised hosts. The search for safe vaccine adjuvants that increase their effectiveness at the mucosal level is a problem of great scientific relevance today.